Efficacy of certolizumab pegol across baseline rheumatoid factor subgroups in patients with rheumatoid arthritis: Post-hoc analysis of clinical trials - İNANÇ, GÜZİDE NEVSUN (My University, 2023)
Aim: Certolizumab pegol (CZP), an Fc-free, PEGylated tumor necrosis factor inhibitor (TNFi), has shown rapid and sustained reduction in signs and symptoms of rheumatoid arthritis (RA). Elevated rheumatoid factor (RF) level has been associated with RA disease progression and poorer TNFi response. We assessed the efficacy of CZP in patients with early and established RA across baseline RF levels.Methods: This post-hoc analysis included data from 6 trials: C-OPERA (NCT01451203), pooled RAPID trials (RAPID-1 [NCT00152386], RAPID-2 [NCT00160602], J-RAPID [NCT00791999], RAPID-C [NCT02151851]), and EXXELERATE (NCT01500278). Patients who received CZP or placebo/comparator with methotrexate (MTX) were categorized by baseline RF quartiles. Efficacy was assessed with Disease Activity Score-28 erythrocyte sedimentation rate (DAS28-ESR).Results: Overall, 316, 1537, and 908 patients were included in C-OPERA, pooled RAPID trials, and EXXELERATE, respectively. Patient demographics and baseline disease characteristics were similar between treatment groups and across RF quartiles. DAS28-ESR low disease activity (LDA) and remission (REM) rates were numerically higher in the CZP + MTX group than PBO + MTX group at weeks 12 and 24, across RF quartiles. LDA and REM rates in the CZP + MTX groups were comparable across RF quartiles at weeks 12 and 24. Mean DAS28-ESR decreased from week 0 to week 24 in the CZP + MTX groups, across RF quartiles.Conclusion: CZP showed steady efficacy across baseline RF quartiles in patients with early and established RA, over 24 weeks. CZP treatment may be considered in patients with RA irrespective of baseline RF levels and time from diagnosis.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; İmmünoloji ve Romatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Immunology and Rheumatology; Health Sciences; ROMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); RHEUMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Romatoloji; Rheumatology; certolizumab pegol; rheumatoid arthritis; rheumatoid factor; tumor necrosis factor inhibitor; TUMOR-NECROSIS-FACTOR; DOUBLE-BLIND; PLUS METHOTREXATE; PHASE-III; C-OPERA; SAFETY; CLASSIFICATION; CRITERIA; certolizumab pegol; rheumatoid arthritis; rheumatoid factor; tumor necrosis factor inhibitor